2022
DOI: 10.1111/nmo.14381
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging assessed enteric motility and luminal content analysis in patients with severe bloating and visible distension

Abstract: Background: Gastrointestinal symptoms in functional gut disorders occur without any discernible structural gut abnormality. Preliminary observations on enteric MRI suggest possible abnormal content and motility of the terminal ileum (TI) in constipationpredominant IBS (IBS-C) with severe bloating, and in functional bloating and distension (FABD) patients. We investigated whether MRI can quantify differences in small bowel (SB) content and motility between patients and healthy controls (HCs). Methods: 11 IBS-C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
1
0
1
Order By: Relevance
“…Using a novel multi-segmental MRI framework, we observed several differences between patients and a healthy volunteer population. While previous studies have reported MRI examinations of several segments of the gut, we added more structural and functional details with the multi-segmental gut examination resulting in a detailed panenteric characterization of the gut [ 10 , 34 , 35 ]. We observed significant differences in static parameters as diabetic patients showed lower stomach volumes at baseline, characterized by lower volumes in the fundus and antrum.…”
Section: Discussionmentioning
confidence: 99%
“…Using a novel multi-segmental MRI framework, we observed several differences between patients and a healthy volunteer population. While previous studies have reported MRI examinations of several segments of the gut, we added more structural and functional details with the multi-segmental gut examination resulting in a detailed panenteric characterization of the gut [ 10 , 34 , 35 ]. We observed significant differences in static parameters as diabetic patients showed lower stomach volumes at baseline, characterized by lower volumes in the fundus and antrum.…”
Section: Discussionmentioning
confidence: 99%
“…En años recientes, utilizando otras tecnologías, como por ejemplo la resonancia magnética, se ha demostrado una disminución de la motilidad del íleon terminal con un aumento de su contenido luminal, sugiriendo una reducción en su aclaramiento o un reflujo del contenido colónico, lo cual puede estar relacionado con los síntomas de estreñimiento y distensión abdominal subjetiva 32 . Con el uso de la cápsula SmartPill ® de pH/presión, y la prueba del aliento con lactulosa, DuPont et al 33 reportaron que el 76% de 46 pacientes con SII presentaron vaciamiento gástrico prolongado, y aquellos con predominio de estreñimiento mostraron tránsito intestinal retardado.…”
Section: Alteraciones De La Motilidad Del Intestino Delgado En El Siiunclassified